PENGARUH KEPERCAYAAN, KEMUDAHAN PENGGUNAAN DAN RISIKO BERTRANSAKSI TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE - Alfiani Hidayat Bakhri, 12.05.51.0119; Soliha, Euis (Students Journal of Economic and Management, 2016)
The study of a very important purchasing decisions made by businessmen who market their products online. The purpose of the study was to analyze the influence of trust, convenience and perception of risk on purchasing decisions online. A sample of 100 respondents, using a non-probability sampling technique with the sampling method used is purposive sampling, its sampling with the criteria that the respondent is an adult and has been making purchases online. Methods of research data analysis using linear regression. The test results showed that there are significant positive effect between trust in online purchasing decisions, there is a positive and significant influence between convenience on purchase decisions online and there are negative and significant effect between the perception of risk on purchasing decisions online.. Â  Keywords: trust, convenience, risk perception and purchasing decisions online.